2002
DOI: 10.1093/aje/kwf158
|View full text |Cite
|
Sign up to set email alerts
|

Hostility Predicts Recurrent Events among Postmenopausal Women with Coronary Heart Disease

Abstract: Psychosocial characteristics may be associated with an increased risk of coronary heart disease (CHD). Whether hostility predicts recurrent coronary events is unknown. A total of 792 women in the Heart and Estrogen/progestin Replacement Study (HERS) were evaluated prospectively to determine the role of hostility as a risk factor for secondary CHD events (nonfatal myocardial infarction and CHD death). The mean age of study participants was 67 years, and the average length of follow-up was 4.1 years. The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…This was supported by a population-based study of Haas et al (2005). In contrast, other studies indicate that hostility is independently of other CAD risk factors associated with nonfatal myocardial infarction and recurrent events in postmenopausal women with CAD (Lahad et al 1997;Chaput et al 2002).…”
Section: Psychosocial Cardiac Risk Factorsmentioning
confidence: 75%
“…This was supported by a population-based study of Haas et al (2005). In contrast, other studies indicate that hostility is independently of other CAD risk factors associated with nonfatal myocardial infarction and recurrent events in postmenopausal women with CAD (Lahad et al 1997;Chaput et al 2002).…”
Section: Psychosocial Cardiac Risk Factorsmentioning
confidence: 75%
“…6 In healthy postmenopausal women, anger suppression and hostility predicted carotid intima-media thickness (IMT), 14 and hostility was predictive of recurrent CAD events in postmenopausal women with coronary disease. 15 Hostility also was related to ambulatory ischemia in a small sample of female subjects 16 but was not predictive of myocardial infarction (MI) in a small sample of women with premature acute MI. 17 Prior studies have demonstrated that hostility is moderately associated with other measures of negative emotion, such as anxiety and depression, 18 and that measures of negative emotion can be associated with anginal symptom reports and poor quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The preponderance of evidence supports an important role for hostility. It is associated with the development of CHD (18 -20), recurrent CHD (21), coronary artery calcification (22), CHD risk factors (23)(24)(25)(26)(27) and all-cause mortality (18,19,28), especially in prospective studies started on older samples (29,30). There are also four negative prospective studies (31)(32)(33)(34) that are discussed by Barefoot in (35).…”
Section: Introductionmentioning
confidence: 99%